Axiomatic Approach in Developing the Filial Care Theory - Uy, Huemer O.; Palompon, Daisy R. (Journal of Community Development Research (Humanities and Social Sciences); Vol 14 No 1 (2021): January - March 2021DO - 10.14456/jcdr-hs.2021.6, 2020)
Filial Piety refers to the special obligations that children have towards their ageing parents, and by extension may include obligations of adopted children and grandchildren. This study aims to design a theory that attempts to explain why filial care responsibility exists and evolves over time. The theory was developed using an axiomatic approach where five axioms were deduced into four emergent propositions. It is theorized that filial care responsibility is a socially-driven act, as its fulfillment is a conformity to implied social contracts in order to ascertain one’s belongingness to a group, and it also promotes the relationship between family members in a form of reciprocated care. As culture and societies advance, values and perceptions toward older persons progress, thus evolving the form of filial care practices, without affecting its essence. Keywords : Filial Piety, Filial Responsibility, Older Persons, Care of Older Persons, Axiomatic Theory Development